1998
DOI: 10.1021/jp982413g
|View full text |Cite
|
Sign up to set email alerts
|

Stable Binding of DNA to Zwitterionic Lipid Bilayers in Aqueous Solutions

Abstract: We found that DNA molecules bind strongly to zwitterionic dipalmitoylphosphatidylcholine lipid bilayers in solutions, facilitating in situ imaging with an atomic force microscope. The binding strength has a lower limit of about 2 kT per helical turn with kT the thermal energy at room temperature. The height of membrane-bound DNA is the same as the diameter of DNA, indicating no compression by the tip at a probe force of about 0.1 nN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
30
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 24 publications
5
30
1
Order By: Relevance
“…This study also predicted equal probabilities for the existence of TAP or PC groups around DNA phosphates. Stable binding of DNA to PC bilayers due to the tethering of DNA by the PC headgroup has also been reported (37). Interestingly, this binding was drastically reduced by a brief exposure to 1 M NaCl because of the screening of the attractive forces between DNA phosphates and PC nitrogens by high concentrations of monovalent ions.…”
Section: Discussionmentioning
confidence: 75%
“…This study also predicted equal probabilities for the existence of TAP or PC groups around DNA phosphates. Stable binding of DNA to PC bilayers due to the tethering of DNA by the PC headgroup has also been reported (37). Interestingly, this binding was drastically reduced by a brief exposure to 1 M NaCl because of the screening of the attractive forces between DNA phosphates and PC nitrogens by high concentrations of monovalent ions.…”
Section: Discussionmentioning
confidence: 75%
“…Although double-stranded DNA (dsDNA) has been shown to bind to zwitterionic lipids (Malghani and Yang, 1998), its thermodynamic stability features remain to be elucidated. Only results obtained with unilamellar DPPC vesicles have been presented, in the light of recent evidence for their better performance in gene delivery studies with respect to internalization mechanisms (Templeton, 2001).…”
Section: Resultsmentioning
confidence: 99%
“…Safinya's investigations also revealed that the L C -H II C phase transition could be mediated by changing the spontaneous curvatures of lipids and membrane rigidity [5]. Since the synthetic cationic lipids are toxic to cell, using liposomes completely composed of zwitterionic lipids (ZL) has been progressively examined as a promising alternative to cationic lipids [14][15][16][17][18][19][20][21][22][23][24][25]. Nevertheless owing to weak interactions, when DNA is added into ZL aqueous solution, only a small amount of DNA is capable of entrapped within the ZL liposomes [23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Since the synthetic cationic lipids are toxic to cell, using liposomes completely composed of zwitterionic lipids (ZL) has been progressively examined as a promising alternative to cationic lipids [14][15][16][17][18][19][20][21][22][23][24][25]. Nevertheless owing to weak interactions, when DNA is added into ZL aqueous solution, only a small amount of DNA is capable of entrapped within the ZL liposomes [23][24][25]. Recently, to enhance the DNA-ZL interaction, divalent metal cations (M n 2+ ) have been used to bridge DNA and ZLs [17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation